Application of Teachers' Creative Pedagogical Learning Approaches to Optimize Students' Interest in Learning at MAN Insan Intellectuals, Palu City - Kalena, Diana Anggriani Kalena; Sunarto Amus; Dhevy Puswiartika (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The role of the teacher is in providing varied activity choices, it is hoped that the goal will be interest in learning. The first problem formulation of this research is: How is the description of students' interest in learning before implementing the creative pedagogical approach at MAN Insan Scholar, Palu City, How can the implementation of the creative pedagogical learning approach optimize students' interest in learning at MAN Insan Scholar, Palu City, What is the description of students' interest in learning after implementing the approach? creative pedagogy at MAN Insan Scholar Palu City. Is the application of a creative pedagogical approach effective in optimizing student interest in learning at MAN Insan Scholar Palu City. The aim of this research is that the implementation of a creative pedagogical learning approach can optimize students' interest in learning at MAN Insan Intellectuals, Palu City. The research method is a quantitative approach because it is used to solve the problems faced and is carried out carefully and systematically, and the data collected is in the form of a series or collection of numbers. Based on the results of the hypothesis, it shows that Sig .( 2-tailed) < 0.05, namely 0.000 < 0.05, then the hypothesis is accepted, because Sig.(2-tailed) is below 0.05. So it can be concluded that there is an influence of using a creative pedagogical learning approach on the learning outcomes of Civics class XI students at MAN Insan Scholar, Palu City.